Structure-Function Relationship of XCL1 Used for in vivo Targeting of Antigen Into XCR1+ Dendritic Cells - Kroczek, Arthur L.; Hartung, Evelyn; Gurka, Stephanie; Becker, Martina; Reeg, Nele; Mages, Hans W.; Voigt, Sebastian; Freund, Christian; Kroczek, Richard A. (Frontiers in Immunology, 2018)
XCL1 is the ligand for XCR1, a chemokine receptor uniquely expressed on cross-presenting dendritic cells (DC) in mouse and man. We are interested in establishing therapeutic vaccines based on XCL1-mediated targeting of peptides or proteins into these DC. Therefore, we have functionally analyzed various XCL1 domains in highly relevant settings in vitro and in vivo. Murine XCL1 fused to ovalbumin (XCL1-OVA) was compared to an N-terminal deletion variant lacking the first seven N-terminal amino acids and to several C-terminal (deletion) variants. Binding studies with primary XCR1+ DC revealed that the N-terminal region stabilizes the binding of XCL1 to its receptor, as is known for other chemokines. Deviating from the established paradigm for chemokines, the N-terminus does not contain critical elements for inducing chemotaxis. On the contrary, this region appears to limit the chemotactic action of XCL1 at higher concentrations. A participation of the XCL1 C terminus in receptor binding or chemotaxis could be excluded in a series of experiments. Binding studies with apoptotic and necrotic XCR1-negative cells suggested a second function of XCL1 for marking of stressed cell for uptake into cross-presenting DC. In vivo studies using CD8+ T cell proliferation and cytotoxicity as readouts confirmed the critical role of the N-terminus for antigen targeting, and excluded any involvement of the C-terminus in the uptake, processing, and presentation of the fused OVA antigen. Together, these studies provide basic data on the function of the various XCL1 domains as well as relevant information on XCL1 as an antigen carrier in therapeutic vaccines.